The Creative Life: A Daily Diary Study of Creativity, Affect, and Well-Being in Creative Individuals. Issue 4 (2nd October 2022) - Smith, Kaile; Pickering, Alan; Bhattacharya, Joydeep
ABSTRACT: Participating in creative activities is associated with increased positive emotions and enhanced subjective well-being in general populations. However, these relationships are less understood in the daily lives of creative individuals who regularly engage in both professional creative behaviors and everyday creative experiences. Therefore, in this study, we recruited a sample of creative adults ( N = 290; creative professionals, students studying creative disciplines, and hobbyists engaged in 20+ hours of creative activities per week) who provided daily responses on their creative behaviors, emotions, and flourishing over two weeks. Creative adults were found to be the most creative on days with highly activated positive emotions and increased well-being and were significantly less creative on days with negative emotions. Individuals with higher levels of openness have stronger ties between their emotions and overall daily creativity and everyday creativity than those with lower levels of openness. Increased openness does not appear to have the same moderating effects on professional creativity and emotion relationships. Finally, high conscientiousness and low neuroticism were also found to predict increased levels of creative activity. Overall, these findings provide novel insights into the links between the specific nature of daily creative activities and the personality and subjective well-being of creative individuals.